Enhancing Socio Economic Development Spurred Through STI Policy Framework Into the Nucleus Off Mainstream Society in Malaysia - Ariffin, Aini Suzana; Ismail, Syuhaida; Ali, Salum S. (Frontiers in Political Science, 2022)
Over the past decades, the Southern Governments have sought to make innovation a key issue in their policy agenda as a catalyst toward sustainable development. Many southern countries realised that innovation with the use of science and technology had a vast potential in the economic transformation of a nation and as means to economic growth. In formulating or implementing innovation policy, it is imperative to identify the possible gaps in the system and set viable interventions in promoting innovation strategic focus. As a matter of fact, innovation is termed as the evolution and implementation of an improved product or service that uses a new marketing approach through rejuvenating the workplace and reengineering the marketing philosophies to cater to the external marketplace. Contemporary nations recognised the role innovation can play in the economic transformation along with incorporating the environmental challenges that are to be faced in due time. Employment growth will accompany innovation as new avenues of study and new knowledge creation exist. Looking at Malaysia, it can be said that the 10-10MySTIE was introduced into the mainstream for the adoption into science, technology, and innovation (STI). Their intentions were admittedly commendable; however, the implementation process was wanting. Policies are the brainchild of a group of people who have adequate knowledge of the subject matter. The implementation roadmap must be clearly charted for any policy to take a life of its own. The common failing in most policies are that policies are well thought of, but a roadmap to realise the policy is seldom implemented and seldom monitored, hence many well-intentioned policies fall by the wayside. Every policy should have an implementation body and a monitoring body who answer directly to the Minister concerned. Whilst crafting a policy, it would be essential that the financial commitment and allocation are identified. For innovation policy to take shape, there is a need to commit to finance to realise the policy, where the systems must be in place, skilled labour must be made available, and where necessary, lure foreign skills to participate in the policy implementation, who are the participants that are required and their availability. Every conceivable actor must be requested to be involved. In implementing or choosing to implement a policy or a series of policies, it is crucial to identify the main actors, subsidiary actors, financial requirements and budgeting, identify the implementers, identify the monitors or monitoring agencies, set up a software programme, as well as churn out a quarterly report and the Minister concerned to sit with the implementers, the monitoring agencies and financial players to gauge the policy progress. In taking a critical view of the policy stage to implementation stage, the need to keep in mind the market segment is critical as innovation and its final product are aimed at attracting the market segment the innovation is targeting. Thus, this paper discusses in detail the enhancement of the socioeconomic development spurred through the STI policy framework into the nucleus off mainstream society toward the achievement of the aforementioned 10-10 MySTIE framework.